Evaluation of antihyperglycemic activities of Bangladeshi medicinal plant Cinnamomum tamala Leaf extracts in alloxan treated Albino Rats - Shibly, Abu Zaffar; Suborna, Laila Arjumand; Adhikari, Juthi; Islam, Md. Shariful (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetic mellitus is a multifactorial disorder associated with its devastating consequences has assumed epidemic proportion in Bangladesh. Methods: The study evaluates the anti-hyperglycemic activity of the aqueous extracts of C. tamala (CTLEt) leaves in blood glucose of albino rats. Type II diabetes mellitus was induced by injecting alloxan at the concentration of 100mg/kg body weight in male albino rats. The diabetic rats were administered orally with aqueous CTLEt at the amount of 1.0ml, 1.5ml and 2.0ml with lab diet and glibenclamide (5mg/kg of body weight). Then blood glucose levels were estimated in all groups after 2 hours, 4 hours, 6 hours, 12 hours and 18 hours of the treatment with CTLEt and a known antidiabetic drug glibenclamide. Results: A comparison was made between the action of CTLEt and glibenclamide. Blood glucose levels of the CTLEt on 18th hours of the study were 8.6 to 5.1mmol/L (1ml CTLEt with lab diet), 10.4 to 4.9mmol/L (1.5ml CTLEt with lab diet), 14.7 to 4.3mmol/L (2.0ml CTLEt with lab diet) in comparison of diabetic control (9.5 to 8.5, 8.7 to 7.8, 7.7 to 7.1mmol/L) and glibenclamide (13.9 to 6.5, 16.3 to 6.1, 9.5 to 5.1mmol/L). Among the sample level, the 2.0ml CTLEt showed a higher efficiency of hypoglycemic effect on alloxan induced diabetic rats. Conclusions: Till date, there is no specific experimental work in Bangladesh about the evolution of antidiabetic activity of C. tamala plant in animal model. Further studies should be undertaken to find out the molecular mechanism of the leaf powder of C. tamala medicinal plant.